Pneumatocoeles after bronchoscopic lung volume reduction with valves. Issue 2 (6th April 2021) - Lestelle, Francois; Fumat, Romane; Didier, Alain; Collot, Samia; Egenod, Thomas; Faviez, Guillaume; Hermant, Christophe; Plat, Gavin; Guibert, Nicolas
Based on the positive results of five randomised controlled trials, bronchoscopic lung volume reduction (BLVR) using Zephyr endobronchial valves (EBV) implantation has been approved for the treatment of patients with severe emphysema and little to no collateral ventilation [1]. These one-way valves produce an atelectasis (or volume reduction) of the target lobe, which leads to decreased hyperinflation and ultimately improvement in exercise capacity. However, EBV therapy is associated with a number of potential adverse events, pneumothorax being the most frequent and threatening complication, occurring in ∼20% of cases [1], and whose treatment is based on chest tube insertion, suction and in cases of prolonged air leaks, valve(s) removal [2]. We report a very rare complication of EBV-induced pneumothorax treatment: a pneumatocoele. We propose a mechanistic explanation and preventive measures. Pneumatocoele is a very rare complication of Zephyr EBV, probably due to chest tube insertion and suction of a trapped and emphysematous lung. Complete healing and functional improvements are possible without the need for valve removal. https://bit.ly/2K84Vjl